2024
DOI: 10.2174/1566523222666220825110147
|View full text |Cite|
|
Sign up to set email alerts
|

SHR6390 Combined with Cabozantinib Inhibits Tumor Progression in the Hepatocellular Carcinoma Mouse Model

Abstract: Background: A novel CDK4/6 inhibitor SHR6390 has shown significant anti-tumor effects. However, its role in hepatocellular carcinoma(HCC) remains unknown. Objective: To explore the inhibitory effect of combination treatment with SHR6390 and cabozantinib in HCC, and its antitumor mechanism, so as to provide more effective therapeutic strategy for HCC patients. Methods: We investigated SHR6390, monotherapy or combined with cabozantinib, by CCK8, wound healing, transwell, western blotting, immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…SHR6390 is an oral, efficient, and selective small molecule CDK4/6 inhibitor, that can induce the inhibition of phosphorylated Rb and cell cycle arrest at the G1 phase in both cell lines and xenografts. 7 In vivo,pharmacodynamics studies show thats SHR6390 can significantly inhibit tumor growth in mouse models of transplanted tumors 8 (including human breast cancer, ovarian cancer, and colon cancers). Pharmacokinetic studies have shown that SHR6390 has high bioavailability in rats and dogs, with a larger apparent volume of distribution, and no significant accumulation after continuous administration.…”
Section: Introductionmentioning
confidence: 99%
“…SHR6390 is an oral, efficient, and selective small molecule CDK4/6 inhibitor, that can induce the inhibition of phosphorylated Rb and cell cycle arrest at the G1 phase in both cell lines and xenografts. 7 In vivo,pharmacodynamics studies show thats SHR6390 can significantly inhibit tumor growth in mouse models of transplanted tumors 8 (including human breast cancer, ovarian cancer, and colon cancers). Pharmacokinetic studies have shown that SHR6390 has high bioavailability in rats and dogs, with a larger apparent volume of distribution, and no significant accumulation after continuous administration.…”
Section: Introductionmentioning
confidence: 99%